Braudel revisited : the Mediterranean world, 1600-1800 - Ruiz, Teofilo F., 1943-; Symcox, Geoffrey; Piterberg, Gabriel, 1955- (University of Toronto Press in association with the UCLA Center for Seventeenth- and Eighteenth-Century Studies and the William Andrews Clark Memorial Library, 2010)
"Fernand Braudel (1912-1985), was a leading French historian and author of, among other books, the groundbreaking The Mediterranean and the Mediterranean World in the Age of Philip II (1949). One of the founders of the Annales School in France, Braudel insisted on treating the Mediterranean region as a whole, irrespective of religious and national divides. Braudel's new historiography rejected political history as the dominant discipline and espoused a 'total history' or a 'history from below' that would tell the story of the vast majority of humanity hitherto excluded from the grand narrative. At the time of the book's appearance, this premise was revolutionary
Keywords: Braudel, Fernand.; Braudel, Fernand. -- Méditerranée et le monde méditerranéen à l'époque de Philippe II.; Braudel, Fernand; Méditerranée et le monde méditerranéen à l'époque de Philippe II (Braudel, Fernand); Historiography.; Historians -- France.; Mediterranean Region -- History -- 1517-1789.; Mediterranean Region -- Civilization.; Méditerranée, Région de la -- Histoire -- 1517-1789.; Méditerranée, Région de la -- Civilisation.; Historiographie.; historiography.; HISTORY -- Historiography.; HISTORY -- World.; Civilization; Historians; Historiography; France; Mediterranean Region; 1517-1789; History